Topical treatment of melasma - Bandyopadhyay Debabrata (Wolters Kluwer Medknow Publications, 2009)
Melasma is a common hypermelanotic disorder affecting the face that is associated with considerable psychological impacts. The management of melasma is challenging and requires a long-term treatment plan. In addition to avoidance of aggravating factors like oral pills and ultraviolet exposure, topical therapy has remained the mainstay of treatment. Multiple options for topical treatment are available, of which hydroquinone (HQ) is the most commonly prescribed agent. Besides HQ, other topical agents for which varying degrees of evidence for clinical efficacy exist include azelaic acid, kojic acid, retinoids, topical steroids, glycolic acid, mequinol, and arbutin. Topical medications modify various stages of melanogenesis, the most common mode of action being inhibition of the enzyme, tyrosinase. Combination therapy is the preferred mode of treatment for the synergism and reduction of untoward effects. The most popular combination consists of HQ, a topical steroid, and retinoic acid. Prolonged HQ usage may lead to untoward effects like depigmentation and exogenous ochronosis. The search for safer alternatives has given rise to the development of many newer agents, several of them from natural sources. Well-designed controlled clinical trials are needed to clarify their role in the routine management of melasma.